2002
DOI: 10.1002/jsfa.1282
|View full text |Cite
|
Sign up to set email alerts
|

Pastoral and species flavour in lambs raised on pasture, lucerne or maize

Abstract: Variations in diet, age and castration were employed to generate a range of flavours that were chemically analysed to find the cause of 'pastoral' flavour in sheepmeat and its relationship to species flavour. Lambs were raised on pasture (ram or castrate) or on a maize-based or lucerne-based concentrate diet (ram only). They were slaughtered at 132 and 232 days. Fat from animals raised on concentrates had lower proportions of fat-hardening stearic acid and higher proportions of oxidationprone fat-softening ole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
133
5
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(152 citation statements)
references
References 31 publications
8
133
5
6
Order By: Relevance
“…In their study, the protein/non-fibrous carbohydrate ratio was much higher in pasture than in the maize diet. Young et al (2003) reported higher levels of skatole in the perirenal fat of lambs raised on pasture compared to maize-dominated concentrate-fed lambs. In the same study, a third group of lambs fed on a lucerne-dominated concentrate diet with intermediate values of nitrogen/soluble carbohydrate ratio presented (Table 2) and the proportion forage/concentrate in the diet, the protein/soluble carbohydrate ratio would be higher in GL group followed by HL and PH groups.…”
Section: --mentioning
confidence: 87%
See 1 more Smart Citation
“…In their study, the protein/non-fibrous carbohydrate ratio was much higher in pasture than in the maize diet. Young et al (2003) reported higher levels of skatole in the perirenal fat of lambs raised on pasture compared to maize-dominated concentrate-fed lambs. In the same study, a third group of lambs fed on a lucerne-dominated concentrate diet with intermediate values of nitrogen/soluble carbohydrate ratio presented (Table 2) and the proportion forage/concentrate in the diet, the protein/soluble carbohydrate ratio would be higher in GL group followed by HL and PH groups.…”
Section: --mentioning
confidence: 87%
“…In forage-based diets with highprotein/non-fibrous carbohydrate ratios, protein and therefore tryptophan degradation is enhanced, resulting in increased skatole production (Sheath et al, 2001). Differences in skatole formation and tissue accumulation have been reported not only when comparing forage vs. concentrate-based diets (Lane and Fraser, 1999;Young et al, 2003;Priolo et al, 2009), but also between forage diets (Schreurs et al, 2003 and, depending on protein solubility and degradability and on synchronisation of protein and carbohydrate degradation in the rumen.…”
Section: Introductionmentioning
confidence: 99%
“…Formation of skatole results from degradation of tryptophan in the rumen by bacteria (Carlson and Breeze, 1984). The high protein content and the high ratio protein/readily digestible carbohydrates of herbage diets would therefore increase the free tryptophan in the rumen (Young et al, 2003) with consequent higher skatole production. In our study we have observed also an effect of dietary tannins on ruminal skatole concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Skatole (3-methylindole) and indole are compounds found in the adipose tissue of different animals. In pork, skatole is responsible for the unpleasant boar taint (Annor-Frempong et al, 1997a), while in sheep, it is linked with typical species flavour (Young et al, 1997) and pastoral odour and flavour (Young et al, 2003). In ruminants, skatole is formed by ruminal microorganisms and it has been often found at higher concentrations in fat from lambs fed green herbages compared to animals given concentrates (Young et al, 1997 andPriolo et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation